Design and implementation of an indoor solar emulator based low-cost autonomous data logger for PV system monitoring - Oday A. Ahmed; Hussain K Sayed; Kanaan A Jalal; Dhari Y. Mahmood; Waleed H. Habeeb (Institute of Advanced Engineering and Science, 2019)
With the growing interest in renewable energy resources, a various number of studies and development for photovoltaic (PV) systems have investigated to satisfy global needs in energy. The larger interest in PV resources has increased request for suitable apparatus with which to test PV systems. This paper deals with the design of an indoor PV source emulator using an actual PV panel to facilitate PV system testing under real environment conditions. A low-cost Arduino Mega256 microcontroller-based data acquisition system (DAQ) approach has been developed to collect the data in term of voltage, power and current based on different levels of light intensity and temperature as well as under partial shading conditions. Hence, the proposed system is not just a solar emulator but it’s a complete solar emulator-DAQ system that can emulate the sunlight and monitor the PV parameters and then collect and store the data for further research investigation. The proposed monitoring system provides real time update of the solar panel characteristics at any time in the year without relying on the weather changes. This data acquisition system will be of superior interest for undergraduate and graduate students as it is both open-source and ﬂexible. The details design of the proposed PV solar emulator and data logger and its implementation are described.